2011
DOI: 10.1002/er.1928
|View full text |Cite
|
Sign up to set email alerts
|

Green nanotechnology of trends in future energy: a review

Abstract: It is well known that current fossil fuel usage is unsustainable and associated with greenhouse gas production. The amount of the world's primary energy supply provided by renewable energy technologies is urgently required. Therefore, the relevant technologies such as hydrogen fuel, solar cell, biotechnology based on nanotechnology, and the relevant patents for exploiting the future energy for the friendly environment are reviewed. At the same time, it is pointed out that the significantly feasible world's eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(66 citation statements)
references
References 146 publications
(156 reference statements)
0
65
0
1
Order By: Relevance
“…They concluded that desalination energy could be reduced by the use of advanced membrane materials and application of innovative technologies. Guo [16] reviewed the relevant renewable energy technologies such as hydrogen fuel, solar cell, biotechnology based on nanotechnology, and the relevant patents for exploiting the future energy for the friendly environment. From his review, he concluded that if the nanotechnology field mixed with the renewable energy sources, the following points were satisfied:…”
Section: -Using Ultrasonic Vibrationmentioning
confidence: 99%
“…They concluded that desalination energy could be reduced by the use of advanced membrane materials and application of innovative technologies. Guo [16] reviewed the relevant renewable energy technologies such as hydrogen fuel, solar cell, biotechnology based on nanotechnology, and the relevant patents for exploiting the future energy for the friendly environment. From his review, he concluded that if the nanotechnology field mixed with the renewable energy sources, the following points were satisfied:…”
Section: -Using Ultrasonic Vibrationmentioning
confidence: 99%
“…Carbon-based nanomaterials, for example, single or multiwall carbon nanotubes, can be used in supercapacitors, batteries, fuel cells, solar cells, among others to enhance charge transfer processes, and catalytic activities that in turn lead to major performance improvements [3]. Geim and Novoselov received the Nobel Prize in 2010 for inventing graphene, first 2-D material based on one-atom thick carbon layers, which demonstrate remarkable physical properties (e.g., flexible, light, and conductive) relevant to many energy applications, also with potential for low-cost manufacturing.…”
Section: Promise Of Smart Materialsmentioning
confidence: 99%
“…Currently, researchers are optimistic regarding the investigations of numerous types of alternative energy storage methods for addressing energy issues using efficient, relatively inexpensive and eco-friendly nanomaterial [9]. One of the potential types of materials for solid-state storage systems is metal hydrides, which exhibit high energy efficiency.…”
Section: Introductionmentioning
confidence: 99%